A comprehensive runoff variation evaluation system of the Yarlung Zangbo River based on vague sets. Issue 2 (20th September 2021) - Zhang, Xiaolu; Zhang, Linglei; Chen, Min; Li, Dian; Peng, Min; Li, Yong; Li, Jia
Abstract: Runoff processes are the basis for maintaining the safety of river ecosystems. The Yarlung Zangbo River (YZR) faces changes in flow regimes due to the impacts of human activities and climate change, which may threaten its fragile ecosystem. In this study, a new comprehensive system for evaluating runoff variation was constructed to investigate the degree of runoff alternation in the YZR. Based on the data from the primary hydrological stations in the YZR from 1956 to 2000, the assessment indicators of runoff variation were selected by considering the flow, sediment, and water temperature processes. Furthermore, a comprehensive evaluation system for runoff variation was constructed via multiple hydrological analysis methods and vague sets. The results showed that the variation index of the YZR from 2010 to 2013 was 0.15–0.20 compared with the flow regimes of the YZR before 2000, which were within a reasonable range, indicating that the comprehensive runoff conditions of the YZR were not greatly disturbed by human activities such as reservoir construction and river regulation during this period. These results provide a tool for evaluating the runoff change in the YZR and new references for researching runoff variation in other similar watersheds. HIGHLIGHTS: Flow, sediment and water temperature were considered to describe river runoff processes. A comprehensive evaluation system for runoff variation was developed based on vague sets theory. Historical runoff process data were used to establish a natural baseline for variation evolution. This method provides a new reference for further research on river regulation and management. Graphical Abstract